2021
DOI: 10.1177/03015742211029610
|View full text |Cite
|
Sign up to set email alerts
|

Torque Comparison Between Two Passive Self-Ligating Brackets with Respect to Interbracket Wire Dimensions and Types: A Finite Element Analysis

Abstract: Objective: This study aimed to analyze the expression of torque between 2 passive self-ligating brackets by simulating different clinical situations using finite element analysis. Material and Methods: Two passive self-ligating brackets, that is, Damon Q (Ormco, Glendora, California) and Smart Clip (3M Unitek, Monrovia, California), were 3D modeled using micro-computed tomography. ANSYS V14.5 software was used for analysis. Archwire and bracket interactions were simulated to measure torque expression by changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…They concluded that self-ligating brackets, particularly passive self-ligating brackets with 0.022 slots, did not favour torque control due to the larger actual play caused by oversized slots and the inability to press the archwire into the bottom of the slot. 23 Similar results were shown in a study conducted by Morina et al 24 However, a study by Thushar et al compared torque expression between passive and active self-ligating bracket systems and concluded that passive self-ligating brackets, such as Damon Q, exhibited superior torquing characteristics compared to active self-ligating brackets with similar archwires. 25 The variation in results is likely due to the equipment used for torque measurement: previous studies employed orthodontic measurement and simulation system (OMSS), while Thushar et al used FEM.…”
Section: Discussionsupporting
confidence: 73%
“…They concluded that self-ligating brackets, particularly passive self-ligating brackets with 0.022 slots, did not favour torque control due to the larger actual play caused by oversized slots and the inability to press the archwire into the bottom of the slot. 23 Similar results were shown in a study conducted by Morina et al 24 However, a study by Thushar et al compared torque expression between passive and active self-ligating bracket systems and concluded that passive self-ligating brackets, such as Damon Q, exhibited superior torquing characteristics compared to active self-ligating brackets with similar archwires. 25 The variation in results is likely due to the equipment used for torque measurement: previous studies employed orthodontic measurement and simulation system (OMSS), while Thushar et al used FEM.…”
Section: Discussionsupporting
confidence: 73%
“…Increasing the wire length of brackets increases the elastic deformation capability of the archwire. 30 The SmartClip SL3 brackets used in our work were wider mesiodistally than Damon Q brackets. The difference in pain perception results obtained in our study may be due to the width differences in the brackets.…”
Section: Discussionmentioning
confidence: 80%